The Influence Of Financial Performance and Company Growth on The Value of Companies in The Cosmetics Subsector Listed on The Indonesia Stock Exchange For The Period 2020-2023 - Katharina Ayusta Jawing; Nur Ida Iriani; Yuni Setyowati (International Research & Development for Human Beings (IRDH), 2026)
The purpose of this study is to examine the relationship between business value, financial performance and company growth. The company's financial documents provide secondary data, and purposive sampling technique is used to select the sample. Multiple linear regression and traditional assumption test are among the analysis methods used. 19 companies listed on the Indonesia Stock Exchange between 2021 and 2023 are the study population. The findings of the first hypothesis test show that financial performance has a significant and positive effect on Company Value. The second result shows the results of the study, that Company Growth shows an insignificant and negative effect on Company Value. This means that when company growth increases, the value of the Cosmetics sub-sector company decreases. Furthermore, the third hypothesis test shows that the variables Financial Performance and Company Growth simultaneously affect Company Value. These results indicate that investors in assessing the value of a company do not only consider one single factor, but rather look at a combination of the company's financial performance and long-term growth potential.